Angiotensin receptor blockers as tentative SARS‐CoV‐2 therapeutics. Issue 5 (4th March 2020) - Gurwitz, David
Abstract: At the time of writing this commentary (February 2020), the coronavirus COVID‐19 epidemic has already resulted in more fatalities compared with the SARS and MERS coronavirus epidemics combined. Therapeutics that may assist to contain its rapid spread and reduce its high mortality rates are urgently needed. Developing vaccines against the SARS‐CoV‐2 virus may take many months. Moreover, vaccines based on viral‐encoded peptides may not be effective against future coronavirus epidemics, as virus mutations could make them futile. Indeed, new Influenza virus strains emerge every year, requiring new immunizations. A tentative suggestion based on existing therapeutics, which would likely be resistant to new coronavirus mutations, is to use available angiotensin receptor 1 (AT1R) blockers, such as losartan, as therapeutics for reducing the aggressiveness and mortality from SARS‐CoV‐2 virus infections. This idea is based on observations that the angiotensin‐converting enzyme 2 (ACE2) very likely serves as the binding site for SARS‐CoV‐2, the strain implicated in the current COVID‐19 epidemic, similarly to strain SARS‐CoV implicated in the 2002–2003 SARS epidemic. This commentary elaborates on the idea of considering AT1R blockers as tentative treatment for SARS‐CoV‐2 infections, and proposes a research direction based on datamining of clinical patient records for assessing its feasibility.